2012
DOI: 10.3329/bjsir.v47i3.13058
|View full text |Cite
|
Sign up to set email alerts
|

In- vitro regeneration of an important medicinal plant Centella asiatica L. Urban

Abstract: An in vitro multiple shoot regeneration protocol has been developed for Centella asiatica L. Urban from the nodal and shoot tips explants using MS medium with different concentrations and combinations of growth regulators. Multiple shoot regeneration was observed from both the explants on MS containing either BAP alone or in combination with IAA, NAA and Kn. Of the two explants, nodal segment showed comparatively better response towards multiple shoot regeneration. Maximum multiple shoots were found on MS supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In all auxin-cytokinin combinations, the average number of shoots and the average length of shoots both increased significantly. In the instance of Centella asiatica, Jaheduzzaman et al (2012) supported this agreement.…”
Section: Resultsmentioning
confidence: 78%
“…In all auxin-cytokinin combinations, the average number of shoots and the average length of shoots both increased significantly. In the instance of Centella asiatica, Jaheduzzaman et al (2012) supported this agreement.…”
Section: Resultsmentioning
confidence: 78%
“…Similar effects were also observed in different other plants (Akter et. al., 2013;Islam et al, 2010;Jaheduzzaman et al, 2012;Khan et al, 2016).The increased amount of decomposed cow dung enriched Nitrogen (N) phosphorus (P), Potasium (K) in soil (Ewulo et al, 2007) which are responsible for root induction of Chrysanthemum (Budiarto and Sulyo, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Root development with an intermediary callus indicated that at that roots and shoots were not well connected with vascular tissue and that plants are insuffi ciently supplied with nutrients (George 1993). Successful rooting in other members of the Apiaceae family was also achieved with 1-5 μM IBA (Tavares et al 2010a, Das et al 2008, Jana and Shekhawat 2011, Coste et al 2012, Jaheduzzaman et al 2012, and with higher concentrations of IBA (Hossain et al 2000, Sharma and Wakhlu 2001, Banerjee et al 1999, Tavares et al 2009-2010, with NAA or IAA (Karuppusamy et al 2007, Jaheduzzaman et al 2012) and only rarely without growth regulators (Makunga et al 2003).…”
Section: Root Initiationmentioning
confidence: 99%
“…A combination of BAP and IBA was used for shoot proliferation of Apiaceae Anethum graveolens (Sharma et al 2004) and Centella asiatica (Banerjee et al 1999), fi rst in a combination of 2.2 μM BAP and 0.5 μM IBA, and second in a combination of 8.9 μM BAP and 0.5 μM IBA (Banerjee et al 1999, Sharma et al 2004). Other researchers (Hosain et al 2000, Nath and Buragohain 2003, Sharma and Wakhlu 2003, Karuppusamy et al 2007, Das et al 2008, Jaheduzzaman et al 2012) used a combination of BAP and NAA or a combination of BAP and IAA (Gaddaguti et al 2013) for proliferation of shoots in Apiaceaes and an optimal concentration ranging from 2 to 17.5 μM of BAP and from 0.5 to 2.7 μM of NAA. The combination of BAP with NAA in our case was not as effective in shoot regeneration.…”
Section: Shoot Multiplicationmentioning
confidence: 99%
See 1 more Smart Citation